Nucleated Teleost Erythrocytes Play an Nk-Lysin- and Autophagy-Dependent Role in Antiviral Immunity - Pereiro, Patricia; Romero, Alejandro; Díaz-Rosales, Patricia; Estepa, Amparo; Figueras, Antonio; Novoa, Beatriz (Frontiers in Immunology, 2017)
With the exception of mammals, vertebrate erythrocytes are nucleated. Nevertheless, these cells are usually considered as mere carriers of hemoglobin. In this work, however, we describe for the first time an unrecognized role of teleost red blood cells (RBCs). We found that Nk-lysin (Nkl), an antimicrobial peptide produced by NK-cells and cytotoxic T-lymphocytes, was also expressed in flatfish turbot (Scophthalmus maximus) erythrocytes. Although the antiviral role of Nkl remains to be elucidated, we found a positive correlation between the transcription of nkl and the resistance to an infection with Rhabdovirus in a teleost fish. Surprisingly, Nkl was found to be present in the autophagolysosomes of erythrocytes and therefore, this higher resistance provided by Nkl could be related to autophagy. The organelles of RBCs are degraded through autophagy during the maturation process of these cells. In this work, we observed that the blockage of autophagy increased the replication of VHSV in nucleated teleost erythrocytes, which suggests that this mechanism may also be a key process in the defense against viruses in these cells. Nkl, which possesses membrane-perturbing ability and was affected by this modulation of RBC autophagy, could also participate in this process. For the first time, autophagy has been described not only as a life cycle event during the maturation of erythrocytes but also as a pivotal antiviral mechanism in nucleated erythrocytes. These results suggest a role of erythrocytes and Nkl in the antiviral immunity of fish and other vertebrates with nucleated red blood cells.